Successful Pudendal Nerve Block and Radiofrequency in 4 Years Scrotal Pain Resistant to Treatment and Three Varicocelectomies: A Case Report - Yang Yang Endro Arjuna; Tasya Meidy Pradhana; Yusak Mangara Tua Siahaan (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Only a small percentage of patients (2-10%) report pain symptoms during varicocele or post-varicocelectomy. The cause of the pain remains unclear and is still a matter of debate. Neither conservative nor surgical treatments provide a conclusive solution for pain. Nerve blocks can serve as a diagnostic and therapeutic tool in cases where the origin of pain is unknown. Case: A 30-year-old male presented with 4 year history of chronic scrotal pain, worsening over the past three weeks. The pain, rated 6/10 on the Numeric Rating Scale (NRS), was unrelieved by rest or analgesics and worsened at night and with prolonged sitting (NRS 7/10), significantly impacting daily activities. He had bilateral recurrent varicocele and underwent three varicocelectomies and ureteroscopy. Oral analgesics and neuropathic pain medications provided only temporary relief. The neurological examination revealed hyperalgesia in the distribution of the pudendal nerve. The imaging results were expected. Discussion: A notable reduction in pain was observed following an ultrasound-guided diagnostic pudendal nerve block with 2 mL of 2% lidocaine, confirming pudendal neuralgia related to varicocele or post-varicocelectomy. The pain is likely due to compression of the pudendal nerve branch by an enlarged pampiniform plexus. Pulsed radiofrequency is utilized to provide longer-lasting pain relief. No complications were reported after the treatment. Conclusion: Pudendal nerve blocks can alleviate scrotal pain and may be an alternative to genitofemoral and ilioinguinal nerve blocks. This is the first report of a successful pudendal nerve block for scrotal pain associated with varicocele or varicocelectomy.